The application of the notion of indirect perpetration through organized structures of power in Latin America and Spain (2011)
In a number of cases before Latin American courts, the notion of indirect perpetration through organized structures of power has been applied after the Juntas Trial. These include several cases relating to crimes committed during the 1976–1983 military regime in Argentina, the case against General Manuel Contreras in Chile, the case against former national senator Alvaro Alfonso García Romero in Colombia and cases against former Shining Path leader Abimael Guzmán and former President Alberto Fujimori in Peru. As a result, although Spanish and Uruguayan courts continue being reluctant to apply it, the notion of indirect perpetration through organized structures of power has come to play today in a number of Latin American jurisdictions a key role in portraying the criminal liability of senior political leaders and high military commanders that make use of the organizations that they control to effect the commission of the crimes.